Kontestasi atas Otoritas Teks Suci Islam di Era Disrupsi: Bagaimana Kelas Menengah Muslim Indonesia Memperlakukan Hadis melalui Media Baru - Rizqa Ahmadi (Jurnal Studi Agama dan Masyarakat, 2019)
This paper was written to become a preliminary record of the hadith debate as one of the sacred texts of Islam in the disruption era. An era marked by the rise of new media, namely alternative media, which in its development has become a new field of religious discourse debate. The debate about Hadith also found its momentum increasingly dynamic. For instance, Muslims in Indonesia use new media to access and make hadith as a lifestyle reference. The emerging of terms such as halal food, syar'i heads carves, halal tourism, ojek syar'i, prophet-style healing, and so on are some examples of them. Unfortunately the existence of this new media indirectly shifts the authority of the Ulama as a reference in understanding the sacred texts, including hadith. This shift emerges to fabrication and distortion of understanding. The contestation of the Hadits authority still revolves around the two main camps: textualism-fundamentalism on the one hand and moderate contextualist- on the other hand. Outside of the two mainstream, the Inkar Sunah group also colored the contestation of hadith authority in new media by middle-class Muslims. Although its voice was not as massive as the two previous groups.